Activation of angiotensin type 2 receptor attenuates testosterone-induced hypertension and uterine vascular resistance in pregnant rats. Issue 1 (19th March 2021) - Mishra, Jay S; Kumar, Sathish
Abstract: Preeclampsia is a pregnancy-related hypertensive disorder with unclear mechanisms. While hypersensitivity to angiotensin II via vasoconstrictive angiotensin type-1 receptor (AT1 R) is observed in preeclampsia, the importance of vasodilatory angiotensin type-2 receptor (AT2 R) in the control of vascular dysfunction is less clear. We assessed whether AT1 R, AT2 R, and endothelial nitric oxide synthase (eNOS) expression are altered in placental vessels of preeclamptic women and tested if ex vivo incubation with AT2 R agonist Compound 21 (C21; 1 μM) could restore AT1 R, AT2 R, and eNOS balance. Further, using a rat model of gestational hypertension induced by elevated testosterone, we examined whether C21 (1 μg/kg/day, oral) could preserve AT1 R and AT2 R balance and improve blood pressure, uterine artery blood flow, and vascular function. Western blots revealed that AT1 R protein level was higher while AT2 R and eNOS protein were reduced in preeclamptic placental vessels, and AT2 R agonist C21 decreased AT1 R and increased AT2 R and eNOS protein levels in preeclamptic vessels. In testosterone dams, blood pressure was higher, and uterine artery blood flow was reduced, and C21 treatment reversed these levels similar to those in controls dams. C21 attenuated the exaggerated Ang II contraction and improved endothelium-dependent vasorelaxation in uterine arteries of testosterone dams. These C21-mediated vascular effects were associated with decreased AT1 R and increased AT2 R and eNOS protein levels. C21 also increased serum nitrate/nitrite and bradykinin production in testosterone dams and attenuated the fetoplacental growth restriction. Thus, AT1 R upregulation and AT2 R downregulation are observed in preeclampsia and testosterone model, and increasing AT2 R activity could help restore AT1 R and AT2 R balance and improve gestational vascular function. Abstract : AT1 R/AT2 R balance is tilted toward vasoconstrictive AT1 R in preeclampsia; restoring this balance using AT2 R agonist mitigates vascular dysfunction in hypertensive pregnant rats, providing a new approach in managing gestational vascular dysfunction.